Acquired hemophilia A in a patient with adult‐onset Still's disease: Successful treatment with steroids. Issue 3 (14th March 2023) - Chebbi, Donia; Marzouk, Sameh; Krichen, Imen; El Ahmer, Ikram; Snoussi, Mouna; Dammak, Chifa; Frikha, Faten; Salah, Raida Ben; Kallel, Choumous; Bahloul, Zouhir
Abstract: Acquired hemophilia A (AHA) is a potentially life‐threatening hemorrhagic disorder with many etiologies. We report the first case in the literature describing the association of AHA with adult‐onset Still's disease (AOSD). Abstract : We report the first case of the literature of acquired hemophilia A associated with adult onset Still's disease, highlighting the importance of the hemostatic follow‐up in systemic diseases in order to guide management and to improve prognosis.